قرآن مجید اور معاش: تفہیمات ازسیرت النبی ﷺ : Quran and livelihood: Understanding from the Life of Prophet Muhammad (SAW) - Dr. Zafar Iqbal (MEI, 2023)
Main topic of Quran is human being. Quran provided complete guidance to human beings for peaceful and well-maintained living. Economic perspective of human life is much important and there are very useful, commands in Quranic text. Some commands are related to earning and some or about expense. The practical explanations or a pictogram of these commands could easily be observed in the Life of Prophet Muhammad (SAW). From Quran and life of the Prophet Muhammad (SAW), one can understand the complete philosophy of Islamic economic circle. Prophet Muhammad’s life provides us a good understanding of Quranic teachings. Many examples from his life could be given that how the commands of halal earning and distributive justice was strictly followed.